Arts Study and Model Eco-Village Silimalombu Samosir Island North Sumatra - Simanullang, Pernandus (Media Wisata, 2023)
Silimalombu Village is one of the areas of Samosir Regency, a residential area with a shift and change of function from green land to construction land, such as new housing. Land that requires reforestation becomes difficult, which turns productive land into unproductive land. In addition, reducing green open space on land construction forces people to optimize their land for productive land. This research examines the eco-village model in the Silimalombu village area as an art management concept to support sustainable village development as one of the eco-village models in the green space village, using qualitative phenomenological research, interpreting objects, and interviews with tourists and residents. The understanding of land use planning is only understood as a horizontal diagram, and land that can be used for production must change the purpose of use and be able to interpret it. Green space is not only realized in the horizontal plane. Still, it can also be used as a vertical space with great flexibility as land that can be transformed into productive land with attractive art management. The art management model is one of several greening programs that can be developed to support environmental (ecological) sustainability and discipline in Silimalombu Village, Samosir Regency